Răspuns :
a) 3 (x-2)^2 = 2x + 4
Folosim (a-b) patrat = a-patrat - 2ab + b-patrat
ptc (a-b)(a-b) = a-patrat - ab - ba + b-patrat
3 ( x-patrat - 4x + 4 ) = 2x + 4
3 x-patrat -12x + 12 = 2x + 4
3 x-patrat -14x + 8 = 0
delta = 14^2 - 4 * 3 * 8 = 196 - 96 = 100 = 10^2
x12 = ( 14 +- 10 ) / 2 * 3 = 4 ; 2/3
Raspuns: 4 si 2/3
(3x - 2) (x+6) = -9
3x*x + 3x*6 - 2*x - 2*6 = -9
3 x-patrat + 16x -12 = -9
3 x-patrat + 16x -3 = 0
delta = 256 + 4 *3 *3 = 256 + 36 = 292 = 17^2
x12 = ( -16 +- 17 ) / 2*3 = 1/6 ; -11/2
Raspuns: 1/6 ; -11/2
Explicație pas cu pas:
a)
3·(x - 2)² = 2x + 4
3·(x² - 4x + 4) = 2x + 4
3x² - 12x + 12 = 2x + 4
3x² - 14x + 8 = 0
Δ = b² - 4ac = (- 14)² - 4 · 3 · 8 = 4 · 49 - 4 · 24 = 4 · 25 = 100
x₁ = (- b + √Δ) / 2a = (14 + 10) / 6 = 24 / 6
x₁ = 4
x₂ = (- b - √Δ) / 2a = (14 - 10) / 6 = 4 / 6
x₂ = 2 / 3
b)
(3x - 2)(x + 6) = - 9
3x² + 18x - 2x - 12 = - 9
3x² + 16x - 3 = 0
Δ = b² - 4ac = 16² - 4 · 3 · (-3) = 4 · 64 + 4 · 9 = 4 · 73
x₁ = (- b + √Δ) / 2a = (- 16 + 2√73) / 6
x₁ = (- 8 + √73) / 3
x₂ = (- b - √Δ) / 2a = (- 16 - 2√73) / 6
x₂ = (- 8 - √73) / 3